Dialysis disequilibrium syndrome (Journal of Bangladesh College of Physicians and Surgeons, 2024)
A clinical constellation of neurologic symptoms and signs that can arise during or soon after dialysis, particularly during the initial stages of the procedure, is known as the dialysis disequilibrium syndrome (DDS). This is an exclusion diagnosis that affects people who are hyperosmolar and uremic; quick correction with renal replacement therapy causes cerebral edema and elevated intracranial pressure, which in turn causes clinical neurologic symptoms. Although DDS is most frequently linked to hemodialysis, it can also happen to individuals who need continuous renal replacement therapy (CRRT) due to acute kidney injury. It hasn't been mentioned in relation to peritoneal dialysis as of now. There is a wide range of signs and symptoms, from headaches and restlessness to coma and death. The specific mechanisms underlying the development of cerebral edema and increased intracranial pressure, which are the principal contributing factors to this illness and the focus of therapy, are still unknown. Once this illness has manifested, treatment is rarely effective. Therefore, taking action to stop it from developing is essential. This review will look at the pathophysiology of this syndrome and address the things to think about to prevent its development.J Bangladesh Coll Phys Surg 2024; 42: 282-288